Developing Reading 3-13 - Beard, Roger (London Hodder and Stoughton, 1990)
Published in an updated version, this book takes account of the implications of the National Curriculum. The book looks at various aspects of the reading process, from approaches to teaching reading, to advice on reading assessment, reading matters and text suitability.
Include Illustrations, Bibliography and Index
Keywords: Developmental reading